2000
DOI: 10.1152/ajpcell.2000.279.4.c981
|View full text |Cite
|
Sign up to set email alerts
|

Oxidants and regulation of K+-Clcotransport in equine red blood cells

Abstract: The effect of oxidants on K(+)-Cl(-) cotransport (KCC) was investigated in equine red blood cells. Carbon monoxide mimicked O(2). The substituted benzaldehyde, 12C79 (5 mM), markedly increased O(2) affinity. In N(2), however, O(2) saturation was low (<10%) but KCC remained active. Nitrite (NO(2)(-)) oxidized heme to methemoglobin (metHb). High concentrations of NO(2)(-) (1 and 5 mM vs. 0.5 mM) increased KCC activity above control levels; it became O(2) independent but remained sensitive to other stimuli. 1-Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Initially, three oxidants were selected to represent a range of different oxidant challenges: XO/HO (2 mmol/l) mixtures to generate extracellular ROS including SOA and hydrogen peroxide (Baskurt et al , 1998; Rogers et al , 2009), PMS to generate SOA intracellularly (Nishikimi et al , 1972; Maridonneau et al , 1983) and NO 2 which promotes formation of methaemoglobin (metHb) (Muzyamba et al , 2000). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, three oxidants were selected to represent a range of different oxidant challenges: XO/HO (2 mmol/l) mixtures to generate extracellular ROS including SOA and hydrogen peroxide (Baskurt et al , 1998; Rogers et al , 2009), PMS to generate SOA intracellularly (Nishikimi et al , 1972; Maridonneau et al , 1983) and NO 2 which promotes formation of methaemoglobin (metHb) (Muzyamba et al , 2000). …”
Section: Resultsmentioning
confidence: 99%
“…These particular oxidants were chosen because of the qualitative differences in oxidative challenge that they present to the red cell. XO/HO mixtures generate SOA and hydrogen peroxide extracellularly (Baskurt et al , 1998; Rogers et al , 2009), whilst PMS generates SOA intracellularly (Nishikimi et al , 1972; Maridonneau et al , 1983); NO 2 oxidises Hb to metHb (Muzyamba et al , 2000); t BHP increases generation of peroxyl and alkoxyl free radicals (Davies, 1989); whilst HOCl produced by myeloperoxidase released from neutorphils may also oxidise membrane thiols (Vissers et al , 1994; Gorudko et al , 2016). Red cell PS exposure is most reliably stimulated by elevation of intracellular Ca 2+ (Bevers & Williamson, 2010) whilst a number of oxidants have previously been shown to increase red cell cation permeability (Gibson & Muzyamba, 2003a,2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Haemoglobin is the major protein of red cells and also reacts reversibly with O 2 making it an obvious candidate [6,7]. A number of observations support a role for Hb, such as the sigmoidal response of some transporters to O 2 tension and the inability of deoxygenation to influence transporter activity following carbon monoxide or nitrite treatment [6,8,9]. In addition, it has been suggested that in sickle cell disease, HbS polymerisation at low O 2 tensions subverts the normal response of transporters such as the K + -Cl À cotransporter (KCC), e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the K + /Cl − cotransporter (KCC) in human erythrocytes increases in activity ~20-fold during erythrocyte oxygenation (23). Moreover, this O 2 -dependent regulation occurs only in whole cells and Hb-containing ghosts, but not in white ghosts or whole cells treated with CO to block O 2 binding (2425). Together with data showing a sigmoidal dependence of K + /Cl − cotransport on O 2 pressure (i.e.…”
mentioning
confidence: 99%